Control And Compensate Interconnected Power Systems Problems Using the Black Hole Optimization Method - Kadhum, Ali Abdyasser (Muhammadiyah University, Sidoarjo, 2025)
The demand for power and energy has been a global problem in the electricity sector for many years while until now, the globally interconnected power systems have suffered from power losses in tie lines and frequency fluctuations. In this paper, two types of controllers, Proportional Integral Derivative (PID) and Sliding Mode Control (SMC), are proposed to overcome the problems in multi-area power systems where These controllers are used to deal with the 5% step load disturbance imposed on the gas turbine output to experiment with the robustness performance of the power system, particularly in turbo-electric propulsion systems and In addition, Load Frequency Control (LFC) is compensated and performance has been improved for 4-zone power systems during outages so finally This review also explores how cosmologically inspired algorithms affect dynamical system control issues, offering a thorough list of control applications along with their inherent benefits and drawbacks.